Trade and Geography in the Spread of Islam. (20th December 2017) - Michalopoulos, Stelios; Naghavi, Alireza; Prarolo, Giovanni
Abstract : This study explores the historical determinants of the spread of Islam. Motivated by a plethora of historical accounts stressing the role of trade for the adoption of Islam, we construct detailed data on pre‐Islamic trade routes to determine this empirical regularity. Our analysis establishes that proximity to the pre‐600 CE trade network is a robust predictor of today's Muslim adherence across countries and ethnic groups in the Old World. We also show that Islam spread successfully in regions ecologically similar to the birthplace of the religion, the Arabian Peninsula, and discuss various mechanisms that may give rise to the observed pattern.